THE EFFECT OF GOOD CORPORATE GOVERNANCE ON COMPANY VALUE WITH FINANCIAL PERFORMANCE AS AN INTERVENING VARIABLE: Study of the Banking Sector Listed in the Indonesian Sharia Stock Index (ISSI) for the 2022-2024 Period - Indah Umiyati; Nadia Anggita (STIESA Press, 2026)
This study aims to examine the effect of Good Corporate Governance (GCG) on firm value, with financial performance as an intervening variable, in the banking sector listed on the Indonesian Sharia Stock Index (ISSI) for the 2022–2024 period. GCG in this study is measured by institutional ownership and an independent board of commissioners. Financial performance is proxied by Return on Assets (ROA), while firm value is proxied by Price to Book Value (PBV). This study uses a quantitative method with a purposive sampling technique to obtain a sample of Islamic banking companies that meet certain criteria. Data analysis was performed using multiple regression using SPSS version 25. The results show that Good Corporate Governance does not have a direct, significant effect on firm value. However, GCG has a significant effect on financial performance, and financial performance has been shown to have a positive effect on firm value. Thus, financial performance acts as a mediating variable in the relationship between GCG and firm value. These findings confirm that good corporate governance improves operational effectiveness and profitability, which ultimately can drive increased firm value. The novelty of this research lies in its focus on the Islamic banking sector, which is a member of the Islamic Financial Services Authority (ISSI) for the 2022–2024 period, thus providing up-to-date empirical evidence on the effectiveness of GCG implementation in creating corporate value in the Islamic capital market.